The role of melatonin on chemotherapy‐induced reproductive toxicity. (23rd November 2017) - Haghi‐Aminjan, Hamed; Asghari, Mohammad Hossein; Farhood, Bagher; Rahimifard, Mahban; Hashemi Goradel, Nasser; Abdollahi, Mohammad
Abstract: Objectives: Reproductive malfunctions after chemotherapy still are a reason of reducing fertility and need specialized intensive care. The aim of this review was to investigate the effect of melatonin on the reproductive system under threatening with chemotherapeutic drugs. Methods: To find the role of melatonin in the reproductive system during chemotherapy, a full systematic literature search was carried out based on Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines in the electronic databases up to 17 April 2017 using search terms in the titles and abstracts. A total of 380 articles are screened according to our inclusion and exclusion criteria. Finally, 18 articles were included in this study. Key findings: It has been cleared that melatonin has bilateral effects on reproductive cells. Melatonin protects normal cells via mechanisms, including decrease in oxidative stress, apoptosis, inflammation and modulating mitochondrial function, and sexual hormones. Furthermore, melatonin with antiproliferative properties and direct effects on its receptors improves reproductive injury and function during chemotherapy. On the other hand, melatonin sensitizes the effects of chemotherapeutic drugs and enhances chemotherapy‐induced toxicity in cancerous cells through increasing apoptosis, oxidative stress and mitochondrial malfunction. Conclusions: The study provides evidence of the bilateral role of melatonin in the reproductive system during chemotherapy.